2004
DOI: 10.1007/s10452-004-0441-2
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of microbial and herbivorous food webs in a coastal sea with special reference to intermittent nutrient supply from bottom intrusion

Abstract: Seasonal changes in abundance of planktonic microorganisms, together with some physico-chemical variables, were monitored monthly from May 1999 to March 2002 in the surface water of a coastal bay where nutrients are mainly supplied by intermittent intrusions of deeper water ͑bottom intrusion͒. No significant bottom intrusion was detected in 1999 but large or frequent bottom intrusions were found from June to October in 2000, and again from mid-June only to late July in 2001. These results indicate that there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…On the other hand, in Japan, many studies about the plankton food web have been reported from coastal waters such as the Ariake Sound (Nakamura & Hirata 2006), Uwa Sea (Nakano et al 2004), Dokai inlet (Uye et al 1998), Seto Inland Sea (Nakamura et al 1994, Uye et al 1996, Ise Bay (Uye et al 2000) and off Usujiri (Shinada et al 2005). A few studies on the seasonal changes in the planktonic food web have been conducted in offshore waters such as in the Kuroshio and adjacent waters (Nakamachi 2003) and in the Oyashio water (Shinada et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in Japan, many studies about the plankton food web have been reported from coastal waters such as the Ariake Sound (Nakamura & Hirata 2006), Uwa Sea (Nakano et al 2004), Dokai inlet (Uye et al 1998), Seto Inland Sea (Nakamura et al 1994, Uye et al 1996, Ise Bay (Uye et al 2000) and off Usujiri (Shinada et al 2005). A few studies on the seasonal changes in the planktonic food web have been conducted in offshore waters such as in the Kuroshio and adjacent waters (Nakamachi 2003) and in the Oyashio water (Shinada et al 2001).…”
Section: Introductionmentioning
confidence: 99%